Angular acceleration of liquid helium II - Chan, S.L. (AIP Publishing, 1970)
Studies have been made of the processes of angular acceleration and retardation of a simply connected volume of helium II at 1.64°K using the technique of second sound attenuation. The acceleration and retardation are found to approach closely to reversibility as compared with experiments where the acceleration is more rapid. A critical velocity for bringing helium II into rotation has been found and the most reliable value for this is (0.047 ± 0.005) cm sec-1 for a cylindrical cavity of radius 2.60 cm. A relaxation time of about 103 sec is found for helium II to come into rotational equilibrium. Persistent currents of long lifetime have also been seen. The results are interpreted in terms of quantized vortices in liquid helium II.